2015
DOI: 10.1007/s13213-015-1189-8
|View full text |Cite
|
Sign up to set email alerts
|

High concentrations of bioavailable heavy metals impact freshwater sediment microbial communities

Abstract: Heavy metal concentrations within freshwater systems can increase as a result of anthropogenic inputs, which in turn can influence microbial community composition and community function. In this study, lake sediments collected from two historically heavy metal impacted geographical regions [Poyang Lake, People's Republic of China (PRC), and sites adjacent to the Muskegon Watershed, MI (USA)] were analyzed for total and available heavy metals (Cd, Cr, Cu, Pb, and Zn), as well as microbial community structure us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(16 citation statements)
references
References 61 publications
1
15
0
Order By: Relevance
“…One of those studies reported the impact of an extreme poly-metallic gradient (including arsenic) on the diversity and distribution of arsenic-related genes in river waters (Desoeuvre et al, 2016 ). Other studies on AMD polluted freshwater sediments (Sánchez-Andrea et al, 2011 ; Jackson et al, 2015 ; Jie et al, 2016 ; Ni et al, 2016 ) showed the dominance of Proteobacteria in microbial communities as well as community specialization. In lake sediments exposed to AMD gradients, the effects of different metals on specific microbes and microbial activities were correlated with their respective chemical properties.…”
Section: Introductionmentioning
confidence: 90%
“…One of those studies reported the impact of an extreme poly-metallic gradient (including arsenic) on the diversity and distribution of arsenic-related genes in river waters (Desoeuvre et al, 2016 ). Other studies on AMD polluted freshwater sediments (Sánchez-Andrea et al, 2011 ; Jackson et al, 2015 ; Jie et al, 2016 ; Ni et al, 2016 ) showed the dominance of Proteobacteria in microbial communities as well as community specialization. In lake sediments exposed to AMD gradients, the effects of different metals on specific microbes and microbial activities were correlated with their respective chemical properties.…”
Section: Introductionmentioning
confidence: 90%
“…). Metal inputs (e.g., as a result of industrial activities) can have strong effects over the abundance of microbial clades (Rastogi et al ., ; Ma et al ., ; Ni et al ., ), which potentially can alter nutrient cycling (Niemeyer et al ., ; Ni et al ., ). Our results were in line with previous findings (Gough and Stahl, ; Niemeyer et al ., ) and revealed a recurrent decrease of 16S rRNA copy numbers for all the enumerated microbial groups in those lakes with metal contamination (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Different experimental system might explain this discrepancy. Most of the previous studies used an enclosed system to test the oxygen consumption after 10 minute-aeration [42,61], which was easy in operation but hardly applied for online OUR monitoring as the wastewater samples required sequential collection. In contrast, our laboratory monitoring system used the batch reactor by injecting wastewater and the activated sludge simultaneously and cultivating the mixture with different HRT (ranging from 1 to 60 min, 10 min for the dose-effect of PTEs), consequently resulting in relative longer exposure of the activated sludge to the toxic substances and lowering the EC50.…”
Section: Dose-effect Of Toxic Substances On the Rourmentioning
confidence: 99%
“…In the present study, the EC 50 of Zn 2+ for the activated sludge (13.40 mg/L) was similar with those obtained from individual bioreporter strains, e.g., 10.9 mg/L by Psychrobacter sp. bioreporters [24] and 16 mg/L by Pseudomonas Shk1 bioreporters [42], but much lower than other previous studies on the activated sludge (around 50 to 60 mg/L) [42,61]. Similarly, the EC 50 of Ni 2+ and phenol in the present study was also lower than previous studies on the activated sludge (21-190 mg/L for Ni 2+ and 416-608 mg/L for phenol) [48,62,63] or by Pseudomonas Shk1 bioreporters (96 mg/L for Ni 2+ and 482 mg/L for phenol) [64,65].…”
Section: Impacts Of Mixed Liquid Suspended Solids (Mlss) On the Rourmentioning
confidence: 99%
See 1 more Smart Citation